Cytogenetics of four Omophoita species (Coleoptera, Chrysomelidae, Alticinae): A comparative analysis using mitotic and meiotic cells submitted to the standard staining and C-banding technique - Almeida, Mara Cristina; Campaner, Carlos; Cella, Doralice Maria [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Omophoita belongs to the tribe Oedionychini and is endemic from Neotropical region. The species of the tribe Oedionychini have revealed certain singular chromosomal features, such as sex chromosomes with extremely large size, asynapsis, and synthetic or amphithelic orientation during meiosis. Additionally, some species also showed post-reductional segregation of the gigantic sex chromosomes in meiotic division. The purpose of this work was to characterize cytogenetically four Omophoita species (O. magniguttis, O. octoguttata, O. personata, and O. sexnotata) in relation to their diploid number, chromosomal morphology, type of sex chromosome system, and constitutive heterochromatin pattern in mitotic and meiotic cells, and compare the obtained data with those of related species to establish the mechanism involved in the chromosomal differentiation of these species during the evolutionary process. The diploid number, 2n = 22 = 20 + X + y, and meiotic formulae, 1 Oil + X + y, observed in these species were similar to those of the same genus and other species related. The autosomal morphology was acrocentric in O. magniguttis and O. octoguttata, metacentric in O. personata, and predominantly metacentric in O. sexnotata. In all these species, the sex chromosomes were metacentric. The secondary constriction occurred in pair 6 and X chromosome of O. personata, and in pair 6 and y chromosome of O. sexnotata. The constitutive heterochromatin was pericentromeric in O. magniguttis and centromeric in O. sexnotata, with the exception of the mitotic sex chromosomes of O. sexnotata, in which centromeric C band was lacking. Additional C bands in the sex chromosomes of O. magniguttis and certain autosomes and sex chromosomes of O. sexnotata were observed. Collochores were indirectly identified in the spermatocytes of O. octoguttata, O. personata, and O. sexnotata. The main mechanisms involved in the karyotype evolution of these species were discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Collochores; Karyotype; Oedionychina; Secondary constriction; Sex chromosomes